2002
DOI: 10.1007/pl00000301
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of rat adjuvant arthritis by therapeutic treatment with bindarit, an inhibitor of MCP-1 and TNF-α production

Abstract: Results obtained indicate that bindarit beneficial effects in experimental arthritis are correlated to MCP-1 and TNF-alpha inhibition and suggest that the control of cytokines and chemokines production can have considerable relevance as regards strategies for the treatment of chronic inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 26 publications
3
48
0
Order By: Relevance
“…Kraan et al showed that IL-8/ CXCL8 was increased in the involved joints compared with the uninvolved joints of patients with RA (25). In a study by Taylor et al, TNF␣ blockade in patients with RA resulted in decreased 111 In-labeled granulocyte migration into affected joints as well as a reduction in the expression of IL-8/CXCL8 in the ST (26). Chemokine networks exist in the RA joint, so that RANTES/CCL5, monocyte chemoattractant protein 1 (MCP-1)/CCL2, or SDF-1/CXCL12 up-regulates RA ST fibroblast expression of IL-8/CXCL8, indicating that chemokines can regulate the expression of other chemokines in the joint (27).…”
Section: Chemokinesmentioning
confidence: 96%
See 1 more Smart Citation
“…Kraan et al showed that IL-8/ CXCL8 was increased in the involved joints compared with the uninvolved joints of patients with RA (25). In a study by Taylor et al, TNF␣ blockade in patients with RA resulted in decreased 111 In-labeled granulocyte migration into affected joints as well as a reduction in the expression of IL-8/CXCL8 in the ST (26). Chemokine networks exist in the RA joint, so that RANTES/CCL5, monocyte chemoattractant protein 1 (MCP-1)/CCL2, or SDF-1/CXCL12 up-regulates RA ST fibroblast expression of IL-8/CXCL8, indicating that chemokines can regulate the expression of other chemokines in the joint (27).…”
Section: Chemokinesmentioning
confidence: 96%
“…Injection of neutralizing MCP-1/CCL2 resulted in reduced macrophage numbers and arthritis in rats with CIA (110). Bindarit, an indazolic derivative inhibitor of TNF␣ and MCP-1/CCL2, inhibited rat AIA (111). Injection of anti-MCP-1/CCL2 preventively resulted in decreased influx of 111 In-labeled T cells into the rat streptococcal cell wall antigeninduced arthritic joint (112).…”
Section: Chemokine Targeting Strategies In Experimental Arthritismentioning
confidence: 99%
“…This suggests that MCP-1 is mainly produced locally by activated cells, where it may exacerbate and sustain inflammation by attracting proinflammatory leukocytes, predominantly monocytes (Stankovic et al, 2009). Substances that can suppress the production of MCP-1 have shown beneficial effects in animal models of arthritis (Guglielmotti et al, 2002;Inoue et al, 2001). A completely different picture was revealed for IL-4.…”
Section: Immunological Markersmentioning
confidence: 99%
“…Similarly, gene transfer of a truncated variant, 7ND, was shown to be efficacious in a mouse model of atherosclerosis [12,13]. Interestingly, the small molecule, bindarit, which specifically decreases levels of CCL2 expression [14], was efficacious in vivo in models of acute pancreatitis [15], lupus [16], and adjuvant-induced arthritis [17], despite its relatively low potency in vitro. However, although blockade of CCR2 with a mAb in the model of collagen-induced arthritis prevented disease when administered prophylactically, it aggravated joint inflammation when given in a therapeutic regimen [18].…”
Section: Introductionmentioning
confidence: 99%